2017
DOI: 10.3847/1538-4357/aa6d11
|View full text |Cite
|
Sign up to set email alerts
|

Resolved Stellar Streams around NGC 4631 from a Subaru/Hyper Suprime-Cam Survey

Abstract: We present the first results of the Subaru/Hyper Suprime-Cam (HSC) survey of the interacting galaxy system, NGC 4631 and NGC 4656. From the maps of resolved stellar populations, we identify 11 dwarf galaxies (including already-known dwarfs) in the outer region of NGC 4631 and the two tidal stellar streams around NGC 4631, named Stream SE and Stream NW, respectively. This paper describes the fundamental properties of these tidal streams. Based on the tip of red giant branch method and the Bayesian statistics, w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 52 publications
(90 reference statements)
3
21
0
1
Order By: Relevance
“…It is an interesting fact, that the derived oxygen abundance of [M/H] = −0.90 in Spur 2 matches almost exactly the metallicity derived for the stellar stream ([M/H] = −0.92; Tanaka et al 2017). The uncertainty for the stellar abundance is quite large, however, with a 90 percent confidence interval between −1.46 and −0.51 (see Tanaka et al 2017). Therefore, this apparent similarity does not provide strong constraints on a possible common origin.…”
Section: Ngc 4627 or Other Satellite Galaxiessupporting
confidence: 67%
“…It is an interesting fact, that the derived oxygen abundance of [M/H] = −0.90 in Spur 2 matches almost exactly the metallicity derived for the stellar stream ([M/H] = −0.92; Tanaka et al 2017). The uncertainty for the stellar abundance is quite large, however, with a 90 percent confidence interval between −1.46 and −0.51 (see Tanaka et al 2017). Therefore, this apparent similarity does not provide strong constraints on a possible common origin.…”
Section: Ngc 4627 or Other Satellite Galaxiessupporting
confidence: 67%
“…This is roughly consistent with the estimate from considering the subpopulation of LV satellites around the MW, M31, CenA, and M81 where satellites of much fainter surface brightness are discoverable via resolved stars. Additionally, using the extremely deep HSC data (∼10 hours of integration on Subaru) from Tanaka et al (2017) for one ELVES host (NGC 4631), we do not find any additional satellites in the ELVES completeness range 14 .…”
Section: Size Distributionsmentioning
confidence: 66%
“…NGC 4631. Tanaka et al (2017) studied the interacting galaxy system NGC 4631 and NGC 4656 and identified 11 dwarf galaxies and two tidal streams in its outer region based on the stellar density maps divided into resolved stellar populations. Seth et al (2005) found somewhat thickened disc structures via HST/ACS observations.…”
Section: Resultsmentioning
confidence: 99%